The Sartul Buryat Dialect: A Preliminary Analysis - Khabtagaeva Bayarma (country:NLD, 2022)
Have you ever wondered what is really happening to minority languages of Northeast Asia and which efforts are being taken both by “westerners” and local people to preserve and promote them? Would you like to discover, uncover, and tackle deep linguistic questions of such small but highly important languages such as Khamnigan Mongol, Wutun, Sartul-Buryat, Tofan and Sakhalin Ainu, just to mention a few? Would you like to know how simple smart phone apps can help communities to preserve, love and use their native language? This book, containing a rich selection of contributions on various aspects of language endangerment, emic and etic approaches at language preservation, and contact-linguistics, is an important contribution to the Unesco's Indigenous Languages Decade, which has right now started (2022-2032)